Chronic inflammation in the etiology of disease across the life span - Furman, David; Campisi, Judith; Verdin, Eric; Carrera-Bastos, Pedro; Targ, Sasha; Franceschi, Claudio; Ferrucci, Luigi; Gilroy, Derek W.; Fasano, Alessio; Miller, Gary W.; Miller, Andrew H.; Mantovani, Alberto; et al. (Nature medicine, 2019)
Although intermittent increases in inflammation are critical for survival during physical injury and infection, recent research has revealed that certain social, environmental and lifestyle factors can promote systemic chronic inflammation (SCI) that can, in turn, lead to several diseases that collectively represent the leading causes of disability and mortality worldwide, such as cardiovascular disease, cancer, diabetes mellitus, chronic kidney disease, non-alcoholic fatty liver disease and autoimmune and neurodegenerative disorders. In the present Perspective we describe the multi-level mechanisms underlying SCI and several risk factors that promote this health-damaging phenotype, including infections, physical inactivity, poor diet, environmental and industrial toxicants and psychological stress. Furthermore, we suggest potential strategies for advancing the early diagnosis, prevention and treatment of SCI. Systemic chronic inflammation increases with age and is linked to the development of several diseases, as presented in this Perspective.